Multiple potential recombination events among Newcastle disease virus genomes in China between 1946 and 2020 - Bahoussi, Amina Nawal; Shah, Pir Tariq; Zhao, Jia-Qi; Wang, Pei-Hua; Guo, Yan-Yan; Wu, Changxin; Xing, Li (Frontiers in Veterinary Science, 2023)
Newcastle Disease Virus (NDV) is a highly adaptable virus with large genetic diversity that has been widely studied for its oncolytic activities and potential as a vector vaccine. Herein, we report the molecular characteristics of 517 complete NDV strains collected from 26 provinces across China between 1946-2020. Phylogenetic analysis revealed the existence of two major groups: GI, which comprises a single genotype Ib, and GII group encompassing eight genotypes (I, II, III, VI. VII. VIII, IX and XII). The Ib genotype is found to dominate China (34%), particularly South and East China, followed by VII (24%) and VI (22%). NDV strains from the two identified groups exhibited great dissimilarities at the nucleotide level of phosphoprotein (P), matrix protein (M), fusion protein (F), and haemagglutinin-neuraminidase (HN) genes. Consistently, the phylogeographic network analysis revealed two main Network Clusters linked to a possible ancestral node from Hunan (strain MH289846.1). Importantly, we identified 34 potential recombination events that involved mostly strains from VII and Ib genotypes. A recombinant of genotype XII isolated in 2019 seems to emerge newly in Southern China. Further, the vaccine strains are found to be highly involved in potential recombination. Therefore, since the influence of recombination on NDV virulence can not be predicted, this report's findings need to be considered for the security of NDV oncolytic application and the safety of NDV live attenuated vaccines.